Rozwód w świetle przepisów The Hindu Marriage Act, 1955 - Delczyk, Dominik (Uniwersytet Wrocławski Koło Doktryn Politycznych i Prawnych, 2023)
The article concerns the provisions of The Hindu Marriage Act, 1955 on divorce. It discusses the personal scope of The Hindu Marriage Act, 1955, the modes of dissolution of marriage provided for therein, and the conditions which entitle a spouse or spouses to exercise each of them.
Keywords: divorce; The Hindu Marriage Act, 1955; dissolution of a marriage; Indian law